Modelo biodinâmico do caminhar humano tendo em vista a interação dinâmica pessoa-estrutura - Costa, Natasha de Paula Amador da (2019)
The theoretical dynamic response of structures induced by human activities such as walking is traditionally determined by considering these actions as periodic moving loads. However, in cases displaying dynamic interaction between structure and pedestrians a biodynamic model is coupled to the structures model, in addition to the applied loads. In view of the mathematical formulation of the pedestrian-structure interaction, a one degree of freedom (consisting of mass, spring and damper) under base excitation is adopted in this work as biodynamic model whose calibration through experimental campaigns is aimed. As a result regression equations were developed allowing the model parameters to be determined on the basis of the pedestrian physical characteristics and its pace frequency. Four types of tests were performed with the aid of a rigid platform and a flexible structure instrumented to measure walking forces of 53 pedestrians: two tests to gather data for the calibration and other two for validation procedures. Simultaneous measurements of force and acceleration of the pedestrian mass center confirmed the model hypothesis and pedestrian responses while walking in a flexible structure showed good correlation to theoretical numerical results obtained by using the proposed biodynamic model.